2010
DOI: 10.1146/annurev.micro.112408.134247
|View full text |Cite
|
Sign up to set email alerts
|

TonB-Dependent Transporters: Regulation, Structure, and Function

Abstract: TonB-dependent transporters (TBDTs) are bacterial outer membrane proteins that bind and transport ferric chelates called siderophores, as well as vitamin B12, nickel complexes, and carbohydrates. The transport process requires energy in the form of protonmotive force and a complex of three inner membrane proteins, TonB-ExbB-ExbD, to transduce this energy to the outer membrane. The siderophore substrates range in complexity from simple small molecules such as citrate to large proteins like serum transferrin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
775
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 803 publications
(820 citation statements)
references
References 94 publications
12
775
0
11
Order By: Relevance
“…Low sequence similarity show that this ExbB-ExbD-mediated iron uptake strategy is probably prevalent among most cyanobacteria species. The Ton transport system has been investigated for over 30 years in non-photosynthetic bacteria, and it is generally thought to be involved in transport of organic compounds such as Fe chelators, as the compounds are too large to pass through porins (Noinaj et al, 2010). For the first time, we have shown that the ExbB-ExbD-dependent transport system has an essential role in inorganic iron uptake in cyanobacteria.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Low sequence similarity show that this ExbB-ExbD-mediated iron uptake strategy is probably prevalent among most cyanobacteria species. The Ton transport system has been investigated for over 30 years in non-photosynthetic bacteria, and it is generally thought to be involved in transport of organic compounds such as Fe chelators, as the compounds are too large to pass through porins (Noinaj et al, 2010). For the first time, we have shown that the ExbB-ExbD-dependent transport system has an essential role in inorganic iron uptake in cyanobacteria.…”
Section: Discussionmentioning
confidence: 95%
“…TonB-ExbB-ExbD-dependent OM transporters are thought to be involved in uptake of organically chelated iron, such as siderophore-iron (Noinaj et al, 2010). To our knowledge, the involvement of this transport system in Fe 0 uptake has not been experimentally verified.…”
Section: Essential Role Of Exbb-exbd In Cyanobacteriamentioning
confidence: 98%
See 3 more Smart Citations